The growth strategy of an alpine beetle: maximization or individual growth adjustment in relation to seasonal time horizons ? - Margraf, Nicolas; Gotthard, Karl; Rahier, Martine (My University, 2003)
1. Life-history theory typically predicts that juvenile growth rate should be maximized and consequently juvenile period minimized. However, in several examples it has been shown that insect larvae do not always grow as fast as they can and this has been explained by costs of high growth rate, typically higher juvenile mortality rate. Hence, some insect larvae have the ability to adaptively adjust growth rate to catch up if development is delayed.
2. The presence of such ability was tested for in the alpine beetle Oreina elongata Suffrian. In this species, the favourable period for development is relatively short and of unpredictable length, and individuals are chemically defended against predation; factors that could affect the balance between the benefits and costs of high growth rate.
3. Here it is shown that when time stressed, O. elongata larvae were able to increase growth rate, accelerate development and reach the normal final weight.
4. Hence, individual growth rate adjustment was present in a situation where its adaptive value appeared to be relatively weak, which supports the notion that flexible growth strategies are a common phenomenon in temperate insects.
Keywords: Growth rate; life history; phenotypic plasticity; photoperiod; seasonality